Polyimide, polyimide film, laminated layer, preparation method of polyimide, polyimide film and laminated layer, and flexible copper-clad plate

By increasing the number of unsaturated conjugated bonds and introducing electron-absorbing groups, the electronic structure of polyimide molecules is regulated, and the purple polyimide material is formed, and the problems of color PI optical defects and insufficient heat resistance in the prior art are solved. , realizes high-performance polyimide materials, suitable for high-frequency and high-speed fields.

CN119176941AActive Publication Date: 2024-12-24HANGZHOU FIRST ELECTRONIC MATERIAL CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411212116.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2024-12-24
Estimated Expiration
2044-08-30

AI Technical Summary

Technical Problem

When the existing polyimide materials prepare color PI, the aggregation of pigment particles leads to optical defects, and the addition of inorganic pigments affects heat resistance, the dispersion process takes a long time and is costly, making it difficult to meet the application needs in the field of high temperatures.

Method used

By increasing the number of unsaturated conjugated bonds in the monomer and introducing electron-drawing groups such as fluorine atoms, trifluoromethyl, chlorine atoms or trichloromethyl, the electronic structure of the polyimide molecule is regulated, and the electron-valued electrons are introduced. Transitions between different energy levels to form a purple color, combining a specific proportion of diamine and dianhydride monomers to design a polyimide material with a purple appearance and excellent properties.

Benefits of technology

It realizes the purple appearance of polyimide material, while improving its optical, electrical, mechanical and thermal properties, reducing dielectric constant and dielectric loss, suitable for high-frequency and high-speed fields, avoiding low thermal stability and poor film Uniform problem.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119176941A_ABST
    Figure CN119176941A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer materials, in particular to polyimide, a polyimide film, a laminated layer, a preparation method thereof and a flexible copper-clad plate. The structural unit of the polyimide comprises residues of dianhydride and residues of diamine; wherein the diamine comprises substituted or unsubstituted biphenyl diamine as shown in a formula (1), and the biphenyl diamine accounts for 80%-100% of the total amount of substance of the diamine; in the formula, R1-R8 are each independently a hydrogen atom, a fluorine atom, a trifluoromethyl group, a chlorine atom, or a trichloromethyl group, and at least one of R1-R8 is not a hydrogen atom; the dianhydride is selected from one or more of 3, 3 ', 4, 4'-biphenyl tetracarboxylic dianhydride, pyromellitic dianhydride and hexafluorodianhydride. According to the polyimide provided by the invention, valence electrons are transitioned among different energy levels to form purple by increasing the number of unsaturated conjugated bonds and introducing an electron withdrawing group. # imgabs0 # formula (1).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a polyimide, a polyimide film, a polyimide laminate, a preparation method thereof, and a flexible copper clad plate. Background Art

[0002] As a high-performance polymer resin, polyimide is a key raw material for flexible printed circuit boards (FPCs) and the electronic circuit industry. It has excellent dimensional stability, excellent high temperature resistance, and good resistance to cold and hot shocks; this is closely related to the fact that its molecular structure contains a large number of high rigidity and high thermal stability functional groups such as benzene ring functional groups and imide ring functional groups. Polyimide materials will appear in different colors such as yellow, khaki, and brown. Polyimides with different optical properties can be used in different fields. Colorless and transparent PI can be used for flexible substrates, black PI can be used for shielding materials, and colored PI can be used for filters, tapes of different colors, labels, and protective films.

[0003] At present, the preparation of colored PI by adding colorants is the mainstream method, but the aggregation of pigment particles can easily lead to optical defects. In order to obtain a better dispersion effect, it is usually necessary to undergo a time-consuming, expensive and complicated modification and dispersion process. In addition, the lower thermal decomposition temperature of organic pigments hinders the application of PI films in high temperature fields. For example, the invention application CN104211974A introduces a method for preparing a colored polyimide film, in which inorganic pigments are dispersed in an organic solvent to obtain a dispersion liquid, monomers are added to the dispersion liquid for polymerization to obtain a polyamic acid solution, and a colored polyimide film is obtained after imidization. However, the addition of inorganic pigments will affect the heat resistance of polyimide, and the dispersion of inorganic pigments is time-consuming and costly.

[0004] In view of this problem, the present invention is proposed. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a polyimide, a polyimide film, a polyimide laminate and a preparation method thereof and a flexible copper clad laminate. The polyimide is a purple polyimide. The polyimide provided by the present invention forms purple by increasing the number of unsaturated conjugated bonds carried by the monomer and introducing electron-withdrawing groups so that valence electrons transition between different energy levels.

[0006] In a first aspect, the structural unit of the polyimide provided by the present invention contains residues of dianhydride and residues of diamine; wherein the diamine comprises substituted or unsubstituted biphenylenediamine represented by formula (1), and the biphenylenediamine accounts for 80% to 100% of the total amount of the diamine.

[0007] Formula (1).

[0008] In the formula, R1 to R8 are each independently a hydrogen atom, a fluorine atom, a trifluoromethyl group, a chlorine atom or a trichloromethyl group, and at least one of R1 to R8 is not a hydrogen atom.

[0009] The dianhydride is selected from one or more of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), pyromellitic dianhydride (PMDA), and hexafluorodianhydride (6FDA).

[0010] The purple polyimide provided by the present invention increases the number of unsaturated conjugated bonds (benzene rings) in the monomer and introduces electron-withdrawing groups (fluorine atoms, trifluoromethyl groups, chlorine atoms or trichloromethyl groups). These design strategies effectively regulate the electronic structure of the polyimide molecule, causing its valence electrons to transition between energy levels within the molecule, thereby producing a specific purple color. The formation of this color not only adds visual uniqueness to the polyimide, but also provides new possibilities for its application in optical materials and other high-performance applications.

[0011] In the present invention, the diphenyl diamine represented by the formula (1) accounts for more than 80% of the total amount of diamines used to synthesize the polyimide, such as 85%, 90%, 95%, 98%, etc., and the remaining diamines may be p-phenylenediamine (p-PDA), m-phenylenediamine (m-PDA), diaminodiphenyl ether (ODA), etc.

[0012] Preferably, the dianhydride is 3,3',4,4'-biphenyltetracarboxylic dianhydride and pyromellitic dianhydride.

[0013] Preferably, the molar ratio of the 3,3',4,4'-biphenyltetracarboxylic acid dianhydride to the pyromellitic acid dianhydride is 9:1 to 7:3; for example, the ratio of 3,3',4,4'-biphenyltetracarboxylic acid dianhydride to pyromellitic acid dianhydride is 8:2, 7:3, 6:4, 5:5, 4:6, 3:7, 2:8, etc. By controlling the molar ratio, the color and peel strength of polyimide (PI) are significantly improved. The effect is not good if it is not within this ratio range. For example, as the ratio of pyromellitic acid dianhydride increases, the color of PI gradually transitions from purple to yellow (L value increases, a value decreases, b value increases), and its peel strength gradually decreases.

[0014] Preferably, in the benzyl diamine represented by formula (1), R 2 , R 3 , R6 and R 7 At least one of them is selected from a fluorine atom, a trifluoromethyl group, a chlorine atom or a trichloromethyl group.

[0015] More preferably, the biphenyl diamine is 4,4-diamino-2,2-bistrifluoromethylbiphenyl (TFMB), 2,2'-dichloro-4,4'-diaminobiphenyl, or 2,2'-difluoro-4,4'-diaminobiphenyl.

[0016] More preferably, the biphenyl diamine is 4,4-diamino-2,2-bistrifluoromethylbiphenyl (TFMB).

[0017] In the present invention, by using preferred biphenyl diamine species, especially 4,4-diamino-2,2-bistrifluoromethylbiphenyl, not only the selection range of suppliers is increased, but also the Dk / Df value can be more effectively reduced than other diamines with different substituents.

[0018] More preferably, the polyimide comprises a structural unit as shown in formula (2).

[0019] Formula (2).

[0020] Wherein, Ar is selected from one or more of the residues of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), the residues of pyromellitic dianhydride (PMDA), and the residues of hexafluorodianhydride (6FDA); R 1 ~R 8 are independently a hydrogen atom, a fluorine atom, a trifluoromethyl group, a chlorine atom or a trichloromethyl group, and R 1 ~R 8 At least one of them is not a hydrogen atom.

[0021] The present invention selects diamine and dianhydride monomers with specific structures to make the polyimide material present the target color (purple), and also shows advantages in optical, electrical, mechanical and thermal performance, and has wide application potential. In addition, the monomers used in the present invention have simple structures, a wide source of raw materials, and low cost.

[0022] Preferably, the degree of polymerization of the polyimide is not less than 25, for example, it may be 30, 50, 80, 100, 150, 200, 500, 1000, etc.

[0023] In a second aspect, the present invention provides a polyimide film comprising the above-mentioned polyimide.

[0024] Preferably, in the Lab value of the polyimide film, L is 50~80, a is 10~40, and b is -15~20; and / or, the dielectric constant of the polyimide film under 10GHz frequency conditions is not higher than 3.20, and the dielectric loss is not higher than 0.0060; and / or, the CTE of the polyimide film is 19~25ppm / K.

[0025] More preferably, in the Lab value of the polyimide film, L is 50~70, a is 20~40, and b is -15~5; and / or, the dielectric constant of the polyimide film under 10GHz frequency conditions is not higher than 3.10, and the dielectric loss is not higher than 0.0050; and / or, the CTE of the polyimide film is 21~23ppm / K.

[0026] In a third aspect, the present invention provides a polyimide laminate, comprising:

[0027] A first polyimide layer.

[0028] A second polyimide layer is coated on the surface of the first polyimide layer.

[0029] and a third polyimide layer covering the surface of the second polyimide layer.

[0030] Each layer of the polyimide stack comprises the above-mentioned polyimide or the above-mentioned polyimide film, wherein the main body of the first polyimide layer and the third polyimide layer is polyimide 1, the main body of the second polyimide layer is polyimide 2, and in the structural unit of the polyimide 2, Ar and R 1 ~R 8 At least one of the groups comprises a trifluoromethyl group.

[0031] Preferably, the fluorine content of the polyimide 2 is greater than 20%, preferably 24.3% to 27.8%. By using the polyimide 2 with the above fluorine content, a low CTE (coefficient of thermal expansion) polyimide can be synthesized more effectively.

[0032] In the present invention, the fluorine content of the polyimide can be calculated according to the following formula represented by formula (6).

[0033] Formula (6).

[0034] In the above formula, n i is the molar amount of aromatic diamine i, n j is the molar amount of tetracarboxylic dianhydride j, M i is the molecular weight of the aromatic diamine after dehydration, M j is the molecular weight of tetracarboxylic dianhydride after dehydration of imine, F i is the number of fluorine atoms contained in one molecule of aromatic diamine i, F j is the number of fluorine atoms contained in one tetracarboxylic dianhydride molecule, and 19.00 is the atomic mass of the fluorine element.

[0035] Preferably, in the Lab value of the polyimide laminate, L is 50-80, a is 10-40, and b is -15-20.

[0036] Preferably, the dielectric constant of the polyimide laminate under 10 GHz frequency conditions is not higher than 3.20, and the dielectric loss is not higher than 0.0060; and / or, the dielectric constant of the first polyimide layer and the third polyimide layer under 10 GHz frequency conditions is 3.00-3.30, and the dielectric loss is 0.0040-0.0060; and / or, the dielectric constant of the second polyimide layer under 10 GHz frequency conditions is 2.85-3.05, and the dielectric loss is 0.0050-0.0065.

[0037] Preferably, the CTE of the polyimide laminate is 19~25ppm / K; and / or, the CTE of the first polyimide layer and the third polyimide layer is greater than 17.5ppm / K> the CTE of the second polyimide layer; preferably, the CTE of the first polyimide layer and the third polyimide layer is 30~65ppm / K; and / or, the CTE of the second polyimide layer is 5~17ppm / K.

[0038] More preferably, in the Lab value of the polyimide laminate, L is 50-70, a is 20-40, and b is -15-5; and / or, the dielectric constant of the polyimide laminate under 10 GHz frequency conditions is not higher than 3.10, and the dielectric loss is not higher than 0.0050; and / or, the dielectric constant of the first polyimide layer and the third polyimide layer under 10 GHz frequency conditions is 3.00-3.20, and the dielectric loss is 0.0040-0.0 055; and / or, the dielectric constant of the second polyimide layer under 10 GHz frequency conditions is 2.85-3.00, and the dielectric loss is 0.0050-0.0060; and / or, the CTE of the polyimide laminate is 21-23 ppm / K; and / or, the CTE of the first polyimide layer and the third polyimide layer is 35-55 ppm / K; and / or, the CTE of the second polyimide layer is 7-15 ppm / K.

[0039] According to the present invention, polyimide laminates are commonly used in flexible copper-clad laminates. The dielectric constant of traditional flexible copper-clad laminates is usually between 3.5 and 4.0, and the dielectric loss is about 2%. The dielectric constant and dielectric loss are large, and the demand for high-frequency signal transmission cannot be met in the field of 5G communications, resulting in signal absorption and loss. Therefore, the development of flexible circuit boards for high-frequency and high-speed fields has become a new research hotspot in the electronic circuit industry. The dielectric constant of common polyimide film materials is about 3.4, and the dielectric loss is about 0.015. However, ordinary polyimide films are difficult to meet the high requirements for the dielectric properties of materials in the future 5G era. The present invention not only takes into account the dielectric properties, but also achieves a purple appearance by developing new polyimide laminate materials. The polyimide layer of the present invention, especially polyimide 1, increases the number of unsaturated conjugated bonds and introduces electron-withdrawing groups to make valence electrons transition between different energy levels to form purple. At the same time, polyimide 2 reduces the dielectric constant by further introducing trifluoromethyl. Moreover, polyimide 2 can be better combined with polyimide 1, so that the entire polyimide laminate not only presents purple, but also has a low dielectric constant and good dimensional stability. At the same time, the CTE (coefficient of thermal expansion) of different layers in the laminate and its matching with the substrate (such as copper foil) are used to effectively reduce the wrinkling and peeling phenomenon. The present invention obtains a polyimide laminate material with excellent comprehensive performance by using the superposition of low dielectric layers and the synergistic effect of each layer. The present invention achieves a balance between the purple appearance and the low dielectric constant and low dielectric loss, and the CTE matches the copper substrate, providing a high-quality new material for high-frequency and high-speed application fields.

[0040] Preferably, the polyimide 2 comprises a structural unit represented by formula (3).

[0041] Formula (3).

[0042] Preferably, the polyimide 2 further comprises structural units represented by formula (4) and / or formula (5).

[0043] Formula (4).

[0044] Formula (5).

[0045] In the formula, R 1 ~R 8 are independently a hydrogen atom, a fluorine atom, a trifluoromethyl group, a chlorine atom or a trichloromethyl group, and R 1 ~R 8 At least one of them is not a hydrogen atom.

[0046] More preferably, in the polyimide 2, the molar proportion of the structural unit represented by formula (3) is 20% to 50%, and the remainder is preferably the structural unit represented by formula (4) and / or formula (5).

[0047] According to the present invention, the preparation method of polyimide can be obtained by imidizing a polyamic acid resin obtained by mixing an aromatic diamine monomer and a dianhydride monomer.

[0048] In a fourth aspect, the present invention also provides a method for preparing the above-mentioned polyimide laminate, comprising forming a first polyimide layer, a second polyimide layer and a third polyimide layer on a substrate to obtain a polyimide laminate; preferably comprising the following steps.

[0049] 1) Preparing a precursor solution of the polyimide 1 and a precursor solution of the polyimide 2 respectively.

[0050] 2) coating a portion of the precursor solution of polyimide 1 on a substrate and drying it, and then simultaneously casting and coating the precursor solution of polyimide 2 and the remaining precursor solution of polyimide 1 on the obtained precursor dry film layer and drying them to obtain a precursor dry film layer of the polyimide laminate.

[0051] 3) thermally curing the substrate coated with the precursor dry film layer of the polyimide laminate.

[0052] Preferably, step 1) comprises mixing a diamine with a solvent to obtain a solution; then adding dianhydride and reacting; and / or, the diamine accounts for 7% to 15% of the total mass of the solution; and / or, the reaction temperature is 0 to 50° C., and the reaction time is 8 to 48 hours; and / or, the ratio of the amount of the dianhydride to the amount of the diamine is 0.960≤≤1.100.

[0053] Preferably, in step 2), the substrate comprises copper foil, aluminum foil, steel strip or polymer support film, the drying temperature is 100-180° C., and the total solvent content in the precursor dry film layer is 15-35 wt %.

[0054] Preferably, in step 3), the thermal curing temperature is 350-400° C., and the thermal curing time is 5-15 min.

[0055] In the present invention, the type of substrate of the polyimide laminate is not limited, for example, it can be a metal substrate such as copper foil, aluminum foil, silver foil, etc., it can also be an inorganic material substrate such as a glass sheet, and it can also be a polymer support film such as a vulcanized fiber substrate and a polyester fiber substrate. Finally, the substrate is removed to obtain the polyimide laminate. When the copper foil is used, the flexible copper clad laminate can be directly obtained without removing the substrate. The copper foil can be an electronic grade rolled copper foil or an electrolytic copper foil, and the thickness of the copper foil is 6 to 50 μm.

[0056] In a fifth aspect, the present invention also provides a flexible copper clad laminate. The flexible copper clad laminate provided by the present invention includes a copper foil and a polyimide layer coated on the surface of the copper foil. The polyimide layer is the above-mentioned polyimide laminate or the polyimide laminate obtained by the above-mentioned preparation method. The surface polyimide of the flexible copper clad laminate provided by the present invention forms a purple color by increasing the number of unsaturated conjugated bonds and introducing electron-withdrawing groups to make valence electrons transition between different energy levels. The middle layer polyimide uses a fluorine-containing monomer to reduce the dielectric constant, and the CTE of the three-layer polyimide is close to the copper foil after combination, so that the flatness and dimensional stability of the flexible copper clad laminate are better. Preferably, the difference between the CTE of the polyimide laminate and the CTE of the copper foil is not more than 8ppm / K. In the present invention, the CTE of the copper foil is 16.6~19.6ppm / K, and the CTE of the polyimide laminate is preferably 19.6~24.7ppm / K.

[0057] The surface polyimide of the present invention increases the number of unsaturated conjugated bonds and introduces electron-withdrawing groups (such as fluorine atoms, trifluoromethyl groups, chlorine atoms, and trichloromethyl groups) to enable valence electrons to transition between different energy levels, thereby forming a purple color. This design not only gives the polyimide a unique color, but also significantly improves its optical properties and stability. The increase in unsaturated conjugated bonds makes the material more stable under light, while the introduction of electron-withdrawing groups further enhances the electronic properties of the material, making it perform well in optoelectronic applications. The middle layer polyimide uses a fluorine-containing monomer, and the introduction of this monomer not only reduces the dielectric constant of the polyimide, but also improves its chemical corrosion resistance and heat resistance. The fluorine-containing monomer has a low polarizability and high electronegativity, so that the middle layer polyimide performs well in high-frequency electrical properties. In addition, the use of fluorine-containing monomers also gives the polyimide better weather resistance and service life. The CTE (coefficient of thermal expansion) of the three-layer polyimide combination is close to that of copper foil, which significantly improves the flatness and dimensional stability of the flexible copper clad laminate when the temperature changes. The design of matching thermal expansion coefficient avoids interlayer stress caused by thermal expansion and contraction, thereby preventing problems such as delamination and cracking of materials. This not only improves the mechanical properties of the copper clad laminate, but also ensures its reliability and durability in long-term use. The present invention significantly improves the performance of polyimide materials in optics, electricity, mechanics and other aspects through ingenious material design and structural optimization. The introduction of unsaturated conjugated bonds and electron-withdrawing groups in the surface polyimide, the selection of fluorinated monomers in the middle layer polyimide, and the matching of thermal expansion coefficients of the three layers of polyimide together give the flexible copper clad laminate excellent flatness, dimensional stability and durability, which is suitable for the manufacture and application of high-performance electronic materials.

[0058] Preferably, the thickness of the polyimide laminate is 6-50 um, and the thickness of the copper foil is 6-50 um.

[0059] Preferably, the thickness of the polyimide laminate is 12-25 μm, and the thickness of the copper foil is 12-25 μm.

[0060] More preferably, the thickness of the first polyimide layer is 1-5 μm, the thickness of the third polyimide layer is 1-5 μm, and the thickness of the second polyimide layer is 4-40 μm.

[0061] More preferably, the thickness of the first polyimide layer is 2-4 μm, the thickness of the third polyimide layer is 2-4 μm, and the thickness of the second polyimide layer is 8-20 μm.

[0062] In a sixth aspect, the method for preparing a flexible copper clad laminate provided by the present invention comprises the following steps.

[0063] 1) Preparing a precursor solution of the polyimide 1 and a precursor solution of the polyimide 2 respectively.

[0064] 2) coating a portion of the precursor solution of polyimide 1 on a long strip of copper foil to volatilize, and then simultaneously casting the precursor solution of polyimide 2 and the remaining precursor solution of polyimide 1 on the obtained precursor dry film layer and drying to obtain the copper foil of the precursor dry film layer of the polyimide laminate.

[0065] 3) thermally curing the copper foil coated with the precursor dry film layer of the polyimide laminate to obtain a long strip of copper foil with the polyimide laminate; and optionally, rolling up the long strip of copper foil with the polyimide laminate.

[0066] Preferably, step 1) comprises dissolving a diamine monomer in a solvent to obtain a solution; and then adding a dianhydride monomer and reacting.

[0067] Preferably, the solvent is selected from highly polar solvents, preferably one or more of N,N-dimethylacetamide, N,N-dimethylformamide, and N-methylpyrrolidone.

[0068] Preferably, the diamine monomer accounts for 7% to 15% of the total mass of the solution.

[0069] Preferably, the reaction temperature is 0-50°C and the reaction time is 8-48h.

[0070] Preferably, the ratio of the amount of the diamine monomer to the amount of the dianhydride monomer is 0.960≤≤1.000.

[0071] Preferably, in step 2), the volatilization temperature is 100-180° C., and the content of the strong polar solvent after volatilization is 15-30 wt %.

[0072] Preferably, in step 3), the thermal curing temperature is 350-400° C., and the thermal curing time is 5-15 min.

[0073] The polyimide, polyimide laminate, preparation method thereof and flexible copper clad laminate provided by the present invention have significantly improved technical effects. The polyimide obtained by the present invention can be copolymerized with a variety of monomers, and a polyimide film having excellent comprehensive properties such as optical properties, dielectric properties and CTE can be obtained at a low cost. Different from the purple polyimide doped with dyes in the prior art, the polyimide of the present invention does not have the problems of low thermal stability and film unevenness. BRIEF DESCRIPTION OF THE DRAWINGS

[0074] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0075] Figure 1 A schematic structural diagram of a purple polyimide flexible copper clad laminate provided in an embodiment of the present invention.

[0076] Among them, 1 is copper foil, 2 is the first polyimide layer, 3 is the second polyimide layer, and 4 is the third polyimide layer. DETAILED DESCRIPTION

[0077] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0078] The following embodiments of the present invention provide a purple polyimide flexible copper clad laminate, the structure of which is shown in FIG. Figure 1As shown, a copper foil 1 is provided at the bottom layer, and a polyimide layer is formed on the surface of the copper foil 1, wherein the polyimide layer includes a first polyimide layer 2 in contact with the copper foil 1, a second polyimide layer 3 coated on the surface of the first polyimide layer 2, and a third polyimide layer 4 coated on the surface of the second polyimide layer 3, wherein the first polyimide layer 2 and the third polyimide layer 4 are prepared from a precursor solution of the polyimide 1, and the second polyimide layer 3 is prepared from a precursor solution of the polyimide 2. The copper foil 1 is a long strip (electronic grade rolled) copper foil, the thickness of the copper foil 1 is 12-25 μm, the thickness of the first polyimide layer 2 is 2-4 μm, the thickness of the second polyimide layer 3 is 8-20 μm, and the thickness of the third polyimide layer 4 is 2-4 μm.

[0079] Example 1

[0080] 1) Precursor solution of polyimide 1: Under nitrogen atmosphere, 0.10 mol of 4,4-diamino-2,2-bistrifluoromethylbiphenyl (TFMB) was dissolved in 200 g of NMP, and after stirring evenly on a stirring table, 0.05 mol of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) was added thereto, and stirred for 1 hour; then 0.03 mol of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) was added, and stirred for 1 hour; then 0.02 mol of pyromellitic dianhydride (PMDA) was added, and stirred at 25°C for 12 hours to obtain a polyamic acid solution, i.e., a precursor solution of polyimide 1.

[0081] 2) Precursor solution of polyimide 2: Under a nitrogen atmosphere, 0.10 mol of 4,4-diamino-2,2-bistrifluoromethylbiphenyl (TFMB) was dissolved in 200 g of NMP, and after stirring evenly on a stirring table, 0.03 mol of hexafluorodianhydride (6FDA) was added thereto, and stirred for 1 hour; then 0.04 mol of pyromellitic dianhydride (PMDA) was added, and stirred for 1 hour; then the remaining 0.03 mol of pyromellitic dianhydride (PMDA) was added, and stirred at 25°C for 12 hours to obtain a polyamic acid solution, i.e., a precursor solution of polyimide 2.

[0082] 3) The precursor solution of polyimide 1 is cast on a long strip of copper foil at a line speed of 5 m / min, and then the solvent is removed in a drying oven at 160° C. for 9 min to obtain a precursor dry film layer of polyimide resin, the solvent content in the precursor dry film layer is 20±2%, and the thickness of the first polyimide layer obtained by imidization is 3 um; then the precursor solution of polyimide 2 and the precursor solution of polyimide 1 are simultaneously cast on the precursor dry film layer at a line speed of 3 m / min, and then the solvent is removed in a drying oven at 160° C. for 15 min to obtain a precursor dry film layer of polyimide resin, the solvent content in the precursor dry film layer is 25±2%; the thickness of the second polyimide layer obtained by imidization is 19 um; the thickness of the third polyimide layer obtained by imidization is 3 um; the total thickness of the polyimide layers obtained by imidization is 25 um.

[0083] 4) The long strip of copper foil coated with the precursor dry film layer of the polyimide resin is heat-treated by heating from 150° C. to 370° C. at a heating rate of about 10° C. / min to imidize the polyamic acid, thereby obtaining a flexible copper-clad laminate.

[0084] Example 2

[0085] The steps of Example 1 were repeated, but the dianhydride compound of polyimide 1 was replaced by 0.07 mol BPDA and 0.03 mol PMDA; the order of addition was 0.03 mol PMDA, 0.04 mol BPDA, and 0.03 mol BPDA. The thickness of the first polyimide layer obtained by imidization was 3 um; the thickness of the second polyimide layer obtained by imidization was 19 um; the thickness of the third polyimide layer obtained by imidization was 3 um; and the total thickness of the polyimide layer obtained by imidization was 25 um.

[0086] Example 3

[0087] The steps of Example 1 were repeated, but the dianhydride compound of polyimide 1 was replaced by 0.09 mol BPDA and 0.01 mol PMDA; the order of addition was 0.01 mol PMDA, 0.06 mol BPDA, and 0.03 mol BPDA. The thickness of the first polyimide layer obtained by imidization was 3 um; the thickness of the second polyimide layer obtained by imidization was 19 um; the thickness of the third polyimide layer obtained by imidization was 3 um; and the total thickness of the polyimide layer obtained by imidization was 25 um.

[0088] Example 4

[0089] The steps of Example 1 were repeated, but the dianhydride compound of polyimide 2 was replaced by 0.02 mol of 6FDA and 0.08 mol of PMDA; the order of addition was 0.02 mol of 6FDA, 0.05 mol of PMDA, and 0.03 mol of PMDA. The thickness of the first polyimide layer obtained by imidization was 3 um; the thickness of the second polyimide layer obtained by imidization was 19 um; the thickness of the third polyimide layer obtained by imidization was 3 um; and the total thickness of the polyimide layer obtained by imidization was 25 um.

[0090] Example 5

[0091] The steps of Example 1 were repeated, but the dianhydride compound of polyimide 2 was replaced by 0.05 mol of 6FDA and 0.05 mol of PMDA; the order of addition was 0.05 mol of 6FDA, 0.03 mol of PMDA, and 0.02 mol of PMDA. The thickness of the first polyimide layer obtained by imidization was 3 um; the thickness of the second polyimide layer obtained by imidization was 19 um; the thickness of the third polyimide layer obtained by imidization was 3 um; and the total thickness of the polyimide layer obtained by imidization was 25 um.

[0092] Example 6

[0093] The method is the same as that of Example 1, except that.

[0094] 1) Precursor solution of polyimide 1: Under nitrogen atmosphere, 0.09 mol of 4,4-diamino-2,2-bistrifluoromethylbiphenyl (TFMB) and 0.01 mol of p-phenylenediamine (PDA) were dissolved in 200 g of NMP, and stirred evenly on a stirring table. Then, 0.05 mol of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) was added thereto, and stirred for 1 hour; then, the remaining 0.03 mol of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) was added, and stirred for 1 hour; then, 0.02 mol of pyromellitic dianhydride (PMDA) was added, and stirred at 25°C for 12 hours to obtain a polyamic acid solution, i.e., a precursor solution of polyimide 1.

[0095] 2) Precursor solution of polyimide 2: Under a nitrogen atmosphere, 0.10 mol of 4,4-diamino-2,2-bistrifluoromethylbiphenyl (TFMB) was dissolved in 200 g of NMP, and after stirring evenly on a stirring table, 0.03 mol of hexafluorodianhydride (6FDA) was added thereto, and stirred for 1 hour; then 0.04 mol of pyromellitic dianhydride (PMDA) was added thereto, and stirred for 1 hour; then 0.03 mol of pyromellitic dianhydride (PMDA) was added thereto, and stirred at 25°C for 12 hours to obtain a polyamic acid solution, i.e., a precursor solution of polyimide 2.

[0096] 3) The precursor solution of polyimide 1 is cast on a long strip of copper foil at a line speed of 5 m / min, and then the solvent is removed in a drying oven at 160° C. for 9 min to obtain a precursor dry film layer of polyimide resin, the solvent content in the precursor dry film layer is 20±2%, and the thickness of the first polyimide layer obtained by imidization is 3 um; then the precursor solution of polyimide 2 and the precursor solution of polyimide 1 are simultaneously cast on the precursor dry film layer at a line speed of 3 m / min, and then the solvent is removed in a drying oven at 160° C. for 15 min to obtain a precursor dry film layer of polyimide resin, the solvent content in the precursor dry film layer is 25±2%; the thickness of the second polyimide layer obtained by imidization is 19 um; the thickness of the third polyimide layer obtained by imidization is 3 um; the total thickness of the polyimide layers obtained by imidization is 25 um.

[0097] 4) The long strip of copper foil coated with the precursor dry film layer of the polyimide resin is heat-treated by heating from 150° C. to 370° C. at a heating rate of about 10° C. / min to imidize the polyamic acid, thereby obtaining a flexible copper-clad laminate.

[0098] Example 7

[0099] The steps of Example 6 were repeated, but the dianhydride compound of polyimide 1 was replaced by 0.07 mol BPDA and 0.03 mol PMDA; the order of addition was 0.03 mol PMDA, 0.04 mol BPDA, and 0.03 mol BPDA. The thickness of the first polyimide layer obtained by imidization was 3 um; the thickness of the second polyimide layer obtained by imidization was 19 um; the thickness of the third polyimide layer obtained by imidization was 3 um; and the total thickness of the polyimide layers obtained by imidization was 25 um.

[0100] Example 8

[0101] The steps of Example 6 were repeated, but the dianhydride compound of polyimide 1 was replaced by 0.09 mol BPDA and 0.01 mol PMDA; the order of addition was 0.01 mol PMDA, 0.06 mol BPDA, and 0.03 mol BPDA. The thickness of the first polyimide layer obtained by imidization was 3 um; the thickness of the second polyimide layer obtained by imidization was 19 um; the thickness of the third polyimide layer obtained by imidization was 3 um; and the total thickness of the polyimide layer obtained by imidization was 25 um.

[0102] Example 9

[0103] The steps of Example 6 were repeated, but the dianhydride compound of polyimide 2 was replaced by 0.02 mol of 6FDA and 0.08 mol of PMDA; the order of addition was 0.02 mol of 6FDA, 0.05 mol of PMDA, and 0.03 mol of PMDA. The thickness of the first polyimide layer obtained by imidization was 3 um; the thickness of the second polyimide layer obtained by imidization was 19 um; the thickness of the third polyimide layer obtained by imidization was 3 um; and the total thickness of the polyimide layer obtained by imidization was 25 um.

[0104] Example 10

[0105] The steps of Example 6 were repeated, but the dianhydride compound of polyimide 2 was replaced by 0.05 mol of 6FDA and 0.05 mol of PMDA; the order of addition was 0.05 mol of 6FDA, 0.03 mol of PMDA, and 0.02 mol of PMDA. The thickness of the first polyimide layer obtained by imidization was 3 um; the thickness of the second polyimide layer obtained by imidization was 19 um; the thickness of the third polyimide layer obtained by imidization was 3 um; and the total thickness of the polyimide layer obtained by imidization was 25 um.

[0106] Embodiment 11

[0107] The method is the same as that of Example 1, except that.

[0108] 1) Precursor solution of polyimide 1: Under nitrogen atmosphere, 0.08 mol of 4,4-diamino-2,2-bistrifluoromethylbiphenyl (TFMB) and 0.02 mol of p-phenylenediamine (PDA) were dissolved in 200 g of NMP, and stirred evenly on a stirring table. Then, 0.05 mol of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) was added thereto, and stirred for 1 hour; then, 0.03 mol of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) was added, and stirred for 1 hour; then, 0.02 mol of pyromellitic dianhydride (PMDA) was added, and stirred at 25°C for 12 hours to obtain a polyamic acid solution, i.e., a precursor solution of polyimide 1.

[0109] 2) Precursor solution of polyimide 2: Under a nitrogen atmosphere, 0.10 mol of 4,4-diamino-2,2-bistrifluoromethylbiphenyl (TFMB) was dissolved in 200 g of NMP, and after stirring evenly on a stirring table, 0.03 mol of hexafluorodianhydride (6FDA) was added thereto, and stirred for 1 hour; then 0.04 mol of pyromellitic dianhydride (PMDA) was added, and stirred for 1 hour; then the remaining 0.03 mol of pyromellitic dianhydride (PMDA) was added, and stirred at 25°C for 12 hours to obtain a polyamic acid solution, i.e., a precursor solution of polyimide 2.

[0110] 3) The precursor solution of polyimide 1 is cast on a long strip of copper foil at a line speed of 5 m / min, and then the solvent is removed in a drying oven at 160° C. for 9 min to obtain a precursor dry film layer of polyimide resin, the solvent content in the precursor dry film layer is 20±2%, and the thickness of the first polyimide layer obtained by imidization is 3 um; then the precursor solution of polyimide 2 and the precursor solution of polyimide 1 are simultaneously cast on the precursor dry film layer at a line speed of 3 m / min, and then the solvent is removed in a drying oven at 160° C. for 15 min to obtain a precursor dry film layer of polyimide resin, the solvent content in the precursor dry film layer is 25±2%; the thickness of the second polyimide layer obtained by imidization is 19 um; the thickness of the third polyimide layer obtained by imidization is 3 um; the total thickness of the polyimide layers obtained by imidization is 25 um.

[0111] 4) The long strip of copper foil coated with the precursor dry film layer of the polyimide resin is heat-treated by heating from 150° C. to 370° C. at a heating rate of about 10° C. / min to imidize the polyamic acid, thereby obtaining a flexible copper-clad laminate.

[0112] Example 12

[0113] The steps of Example 11 were repeated, but the dianhydride compound of polyimide 1 was replaced by 0.07 mol BPDA and 0.03 mol PMDA; the order of addition was 0.03 mol PMDA, 0.04 mol BPDA, and 0.03 mol BPDA. The thickness of the first polyimide layer obtained by imidization was 3 um; the thickness of the second polyimide layer obtained by imidization was 19 um; the thickness of the third polyimide layer obtained by imidization was 3 um; and the total thickness of the polyimide layer obtained by imidization was 25 um.

[0114] Embodiment 13

[0115] The steps of Example 11 were repeated, but the dianhydride compound of polyimide 1 was replaced by 0.09 mol BPDA and 0.01 mol PMDA; the order of addition was 0.01 mol PMDA, 0.06 mol BPDA, and 0.03 mol BPDA. The thickness of the first polyimide layer obtained by imidization was 3 um; the thickness of the second polyimide layer obtained by imidization was 19 um; the thickness of the third polyimide layer obtained by imidization was 3 um; and the total thickness of the polyimide layer obtained by imidization was 25 um.

[0116] Embodiment 14

[0117] The steps of Example 11 were repeated, but the dianhydride compound of polyimide 2 was replaced by 0.02 mol of 6FDA and 0.08 mol of PMDA; the order of addition was 0.02 mol of 6FDA, 0.05 mol of PMDA, and 0.03 mol of PMDA. The thickness of the first polyimide layer obtained by imidization was 3 um; the thickness of the second polyimide layer obtained by imidization was 19 um; the thickness of the third polyimide layer obtained by imidization was 3 um; and the total thickness of the polyimide layer obtained by imidization was 25 um.

[0118] Embodiment 15

[0119] The steps of Example 11 were repeated, but the dianhydride compound of polyimide 2 was replaced by 0.05 mol of 6FDA and 0.05 mol of PMDA; the order of addition was 0.05 mol of 6FDA, 0.03 mol of PMDA, and 0.02 mol of PMDA. The thickness of the first polyimide layer obtained by imidization was 3 um; the thickness of the second polyimide layer obtained by imidization was 19 um; the thickness of the third polyimide layer obtained by imidization was 3 um; and the total thickness of the polyimide layer obtained by imidization was 25 um.

[0120] Example 16

[0121] 1) Precursor solution of polyimide 1: Under nitrogen atmosphere, 0.10 mol of 4,4-diamino-2,2-bistrifluoromethylbiphenyl (TFMB) was dissolved in 200 g of NMP, and after stirring evenly on a stirring table, 0.05 mol of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) was added thereto, and stirred for 1 hour; then 0.03 mol of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) was added, and stirred for 1 hour; then 0.02 mol of pyromellitic dianhydride (PMDA) was added, and stirred at 25°C for 12 hours to obtain a polyamic acid solution, i.e., a precursor solution of polyimide 1.

[0122] 2) Precursor solution of polyimide 2: Under a nitrogen atmosphere, 0.10 mol of 4,4-diamino-2,2-bistrifluoromethylbiphenyl (TFMB) was dissolved in 200 g of NMP, and after stirring evenly on a stirring table, 0.03 mol of hexafluorodianhydride (6FDA) was added thereto, and stirred for 1 hour; then 0.04 mol of pyromellitic dianhydride (PMDA) was added, and stirred for 1 hour; then the remaining 0.03 mol of pyromellitic dianhydride (PMDA) was added, and stirred at 25°C for 12 hours to obtain a polyamic acid solution, i.e., a precursor solution of polyimide 2.

[0123] 3) Precursor solution of polyimide 3: Under nitrogen atmosphere, 0.10 mol of 4,4-diamino-2,2-bistrifluoromethylbiphenyl (TFMB) was dissolved in 200 g of NMP, and after stirring evenly on a stirring table, 0.04 mol of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) was added thereto, and stirred for 1 hour; then 0.03 mol of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) was added, and stirred for 1 hour; then 0.03 mol of pyromellitic dianhydride (PMDA) was added, and stirred at 25°C for 12 hours to obtain a polyamic acid solution, i.e., a precursor solution of polyimide 3.

[0124] 4) The precursor solution of polyimide 1 is cast on a long strip of copper foil at a line speed of 5 m / min, and then the solvent is removed in a drying oven at 160° C. for 9 min to obtain a precursor dry film layer of polyimide resin, the solvent content in the precursor dry film layer is 20±2%, and the thickness of the first polyimide layer obtained by imidization is 3 um; then the precursor solution of polyimide 2 and the precursor solution of polyimide 3 are simultaneously cast on the precursor dry film layer at a line speed of 3 m / min, and then the solvent is removed in a drying oven at 160° C. for 15 min to obtain a precursor dry film layer of polyimide resin, the solvent content in the precursor dry film layer is 25±2%; the thickness of the second polyimide layer obtained by imidization is 19 um; the thickness of the third polyimide layer obtained by imidization is 3 um; the total thickness of the polyimide layers obtained by imidization is 25 um.

[0125] 5) The long strip of copper foil coated with the precursor dry film layer of the polyimide resin is heat-treated by heating from 150° C. to 370° C. at a heating rate of about 10° C. / min to imidize the polyamic acid, thereby obtaining a flexible copper clad laminate.

[0126] Embodiment 17

[0127] 1) Precursor solution of polyimide 1: Under nitrogen atmosphere, 0.10 mol of 4,4-diamino-2,2-bistrifluoromethylbiphenyl (TFMB) was dissolved in 200 g of NMP, and after stirring evenly on a stirring table, 0.05 mol of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) was added thereto, and stirred for 1 hour; then 0.03 mol of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) was added, and stirred for 1 hour; then 0.02 mol of pyromellitic dianhydride (PMDA) was added, and stirred at 25°C for 12 hours to obtain a polyamic acid solution, i.e., a precursor solution of polyimide 1.

[0128] 2) Precursor solution of polyimide 2: Under nitrogen atmosphere, 0.10 mol of 4,4-diamino-2,2-bistrifluoromethylbiphenyl (TFMB) was dissolved in 200 g of NMP, and after stirring evenly on a stirring table, 0.02 mol of hexafluorodianhydride (6FDA) was added thereto, and stirred for 1 hour; then 0.01 mol of biphenyltetracarboxylic dianhydride (BPDA) was added, and stirred for 1 hour; then 0.04 mol of pyromellitic dianhydride (PMDA) was added, and stirred for 1 hour; then 0.03 mol of pyromellitic dianhydride (PMDA) was added, and stirred at 25°C for 12 hours to obtain a polyamic acid solution, i.e., a precursor solution of polyimide 2.

[0129] 3) Precursor solution of polyimide 3: Under nitrogen atmosphere, 0.10 mol of 4,4-diamino-2,2-bistrifluoromethylbiphenyl (TFMB) was dissolved in 200 g of NMP, and after stirring evenly on a stirring table, 0.04 mol of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) was added thereto, and stirred for 1 hour; then 0.03 mol of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) was added, and stirred for 1 hour; then 0.03 mol of pyromellitic dianhydride (PMDA) was added, and stirred at 25°C for 12 hours to obtain a polyamic acid solution, i.e., a precursor solution of polyimide 3.

[0130] 4) The precursor solution of polyimide 1 is cast on a long strip of copper foil at a line speed of 5 m / min, and then the solvent is removed in a drying oven at 160° C. for 9 min to obtain a precursor dry film layer of polyimide resin, the solvent content in the precursor dry film layer is 20±2%, and the thickness of the first polyimide layer obtained by imidization is 3 um; then the precursor solution of polyimide 2 and the precursor solution of polyimide 3 are simultaneously cast on the precursor dry film layer at a line speed of 3 m / min, and then the solvent is removed in a drying oven at 160° C. for 15 min to obtain a precursor dry film layer of polyimide resin, the solvent content in the precursor dry film layer is 25±2%; the thickness of the second polyimide layer obtained by imidization is 19 um; the thickness of the third polyimide layer obtained by imidization is 3 um; the total thickness of the polyimide layers obtained by imidization is 25 um.

[0131] 5) The long strip of copper foil coated with the precursor dry film layer of the polyimide resin is heat-treated by heating from 150° C. to 370° C. at a heating rate of about 10° C. / min to imidize the polyamic acid, thereby obtaining a flexible copper clad laminate.

[0132] Embodiment 18

[0133] The steps of Example 17 were repeated, but the dianhydride compound of polyimide 2 was replaced by 0.02 mol of 6FDA, 0.02 mol of BPDA, and 0.06 mol of PMDA; the order of addition was 0.02 mol of 6FDA, 0.02 mol of BPDA, 0.03 mol of PMDA, and 0.03 mol of PMDA. The thickness of the first polyimide layer obtained by imidization was 3 um; the thickness of the second polyimide layer obtained by imidization was 19 um; the thickness of the third polyimide layer obtained by imidization was 3 um; and the total thickness of the polyimide layer obtained by imidization was 25 um.

[0134] Comparative Example 1

[0135] The method is the same as that of Example 1, except that.

[0136] 1) Precursor solution of polyimide 1: Under nitrogen atmosphere, 0.05 mol of 4,4-diamino-2,2-bistrifluoromethylbiphenyl (TFMB) and 0.05 mol of p-phenylenediamine (PDA) were dissolved in 200 g of NMP, and stirred evenly on a stirring table. Then, 0.05 mol of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) was added thereto, and stirred for 1 hour; then, 0.03 mol of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) was added, and stirred for 1 hour; then, 0.02 mol of pyromellitic dianhydride (PMDA) was added, and stirred at 25°C for 12 hours to obtain a polyamic acid solution, i.e., a precursor solution of polyimide 1.

[0137] 2) Precursor solution of polyimide 2: Under a nitrogen atmosphere, 0.10 mol of 4,4-diamino-2,2-bistrifluoromethylbiphenyl (TFMB) was dissolved in 200 g of NMP, and after stirring evenly on a stirring table, 0.03 mol of hexafluorodianhydride (6FDA) was added thereto, and stirred for 1 hour; then 0.04 mol of pyromellitic dianhydride (PMDA) was added thereto, and stirred for 1 hour; then 0.03 mol of pyromellitic dianhydride (PMDA) was added thereto, and stirred at 25°C for 12 hours to obtain a polyamic acid solution, i.e., a precursor solution of polyimide 2.

[0138] 3) The precursor solution of polyimide 1 is cast on a long strip of copper foil at a line speed of 5 m / min, and then the solvent is removed in a drying oven at 160° C. for 9 min to obtain a precursor dry film layer of polyimide resin, the solvent content in the precursor dry film layer is 20±2%, and the thickness of the first polyimide layer obtained by imidization is 3 um; then the precursor solution of polyimide 2 and the precursor solution of polyimide 3 are simultaneously cast on the precursor dry film layer at a line speed of 3 m / min, and then the solvent is removed in a drying oven at 160° C. for 15 min to obtain a precursor dry film layer of polyimide resin, the solvent content in the precursor dry film layer is 25±2%; the thickness of the second polyimide layer obtained by imidization is 19 um; the thickness of the third polyimide layer obtained by imidization is 3 um; the total thickness of the polyimide layers obtained by imidization is 25 um.

[0139] 4) The long strip of copper foil coated with the precursor dry film layer of the polyimide resin is heat-treated by heating from 150° C. to 370° C. at a heating rate of about 10° C. / min to imidize the polyamic acid, thereby obtaining a flexible copper-clad laminate.

[0140] Comparative Example 2

[0141] The steps of Comparative Example 1 were repeated, but the diamine compound of polyimide 1 was replaced by 0.07 mol of TFMB and 0.03 mol of PDA. The thickness of the first polyimide layer obtained by imidization was 3 um; the thickness of the second polyimide layer obtained by imidization was 19 um; the thickness of the third polyimide layer obtained by imidization was 3 um; and the total thickness of the polyimide layers obtained by imidization was 25 um.

[0142] Comparative Example 3

[0143] The steps of Comparative Example 1 were repeated, but the diamine compound of polyimide 1 was replaced with 0.03 mol of TFMB and 0.07 mol of PDA. The thickness of the first polyimide layer obtained by imidization was 3 um; the thickness of the second polyimide layer obtained by imidization was 19 um; the thickness of the third polyimide layer obtained by imidization was 3 um; and the total thickness of the polyimide layers obtained by imidization was 25 um.

[0144] Comparative Example 4

[0145] The steps of Comparative Example 1 were repeated, but the diamine compound of polyimide 1 was replaced with 0.10 mol of PDA. The thickness of the first polyimide layer obtained by imidization was 3 um; the thickness of the second polyimide layer obtained by imidization was 19 um; the thickness of the third polyimide layer obtained by imidization was 3 um; and the total thickness of the polyimide layers obtained by imidization was 25 um.

[0146] Comparative Example 5

[0147] The steps of Comparative Example 1 were repeated, but the dianhydride compound of polyimide 2 was replaced with 0.10 mol of pyromellitic dianhydride (PMDA); the order of addition was 0.05 mol of PMDA, 0.03 mol of PMDA, and 0.02 mol of PMDA. The thickness of the first polyimide layer obtained by imidization was 3 um; the thickness of the second polyimide layer obtained by imidization was 19 um; the thickness of the third polyimide layer obtained by imidization was 3 um; and the total thickness of the polyimide layer obtained by imidization was 25 um.

[0148] Comparative Example 6

[0149] The steps of Comparative Example 1 were repeated, but the dianhydride compound of polyimide 2 was replaced with 0.03 mol of pyromellitic dianhydride (PMDA) and 0.07 mol of hexafluorodianhydride (6FDA); the order of addition was 0.04 mol of 6FDA, 0.03 mol of 6FDA, and 0.03 mol of PMDA. The thickness of the first polyimide layer obtained by imidization was 3 um; the thickness of the second polyimide layer obtained by imidization was 19 um; the thickness of the third polyimide layer obtained by imidization was 3 um; and the total thickness of the polyimide layer obtained by imidization was 25 um.

[0150] Comparative Example 7

[0151] The steps of Comparative Example 1 were repeated, but the diamine compound of polyimide 1 was replaced with 0.10 mol of 2,2'-difluoro-4,4'-diaminobiphenyl. The thickness of the first polyimide layer obtained by imidization was 3 um; the thickness of the second polyimide layer obtained by imidization was 19 um; the thickness of the third polyimide layer obtained by imidization was 3 um; and the total thickness of the polyimide layers obtained by imidization was 25 um.

[0152] The above embodiments and comparative examples were subjected to performance tests.

[0153] Lab value test: Instrument: Spectrophotometer, Instrument model: Konica Minolta CM-36dg, Test conditions: Reflection measurement (SCI), Wavelength 360~740nm.

[0154] Thermal expansion coefficient (CTE) test: Referring to the IPC-TM-650 2.4.41.3 test standard, 3mm×15mm samples were cut from the polyimide film and the polyimide layer in the support film, and a tensile test was performed at a constant heating rate (10℃ / min) in the temperature range of 30 to 300℃ while applying a load of 0.02N using a thermomechanical analysis (TMA) device (TAInstruments Q400 TMA). The thermal expansion coefficient (×10 -6 / K).

[0155] Dielectric properties (Dk / Df) test: refer to IEC61189-2-721-2015 test standard, use network analyzer (wide temperature, wide frequency impedance analyzer from NOV ONTROL, Germany) for test; cut out 7cm×7cm samples respectively, and treat the samples in a 150℃ circulation oven for 2h. After drying, place the samples in an environment of 25±2℃, 50±3RH% for 2h, then test and record the test results.

[0156] Table 1

[0157] In summary, it can be seen that the polyimide of the present invention can be copolymerized with a variety of monomers to obtain a polyimide film with excellent comprehensive properties such as optical properties, dielectric properties, CTE, etc. Different from the dye-doped purple polyimide in the prior art, the polyimide of the present invention does not have the problems of low thermal stability and film unevenness.

[0158] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A polyimide, characterized in that: The structural unit of the polyimide comprises a residue of a dianhydride and a residue of a diamine; wherein the diamine comprises a substituted or unsubstituted diphenyl diamine represented by formula (1), and the diphenyl diamine accounts for 80% to 100% of the total amount of the diamine; Formula (1) In the formula, R1 to R8 are independently a hydrogen atom, a fluorine atom, a trifluoromethyl group, a chlorine atom or a trichloromethyl group, and at least one of R1 to R8 is not a hydrogen atom; The dianhydride is selected from one or more of 3,3',4,4'-biphenyltetracarboxylic dianhydride, pyromellitic dianhydride, and hexafluorodianhydride.

2. The polyimide according to claim 1, characterized in that The dianhydride is 3,3',4,4'-biphenyltetracarboxylic dianhydride and pyromellitic dianhydride; Preferably, the molar ratio of the 3,3',4,4'-biphenyltetracarboxylic dianhydride to the pyromellitic dianhydride is 9:1 to 1:9, preferably 9:1 to 7:

3.

3. The polyimide according to claim 2, characterized in that In the benzyl diamine represented by formula (1), at least one of R2, R3, R6 and R7 is selected from a fluorine atom, a trifluoromethyl group, a chlorine atom or a trichloromethyl group; Preferably, the biphenyl diamine is 4,4-diamino-2,2-bistrifluoromethylbiphenyl, 2,2'-dichloro-4,4'-diaminobiphenyl, 2,2'-difluoro-4,4'-diaminobiphenyl; More preferably, the biphenyl diamine is 4,4-diamino-2,2-bistrifluoromethylbiphenyl.

4. The polyimide according to any one of claims 1 to 3, characterized in that The polyimide comprises a structural unit as shown in formula (2): Formula (2) In the formula, Ar is selected from one or more of the residues of 3,3',4,4'-biphenyltetracarboxylic dianhydride, the residues of pyromellitic dianhydride, and the residues of hexafluorodianhydride; R1 to R8 are independently hydrogen atoms, fluorine atoms, trifluoromethyl groups, chlorine atoms, or trichloromethyl groups, and at least one of R1 to R8 is not a hydrogen atom; and the degree of polymerization of the polyimide is not less than 25.

5. A polyimide film, characterized in that: A polyimide comprising any one of claims 1 to 4; Preferably, in the Lab value of the polyimide film, L is 50-80, a is 10-40, and b is -15-20; and / or, the dielectric constant of the polyimide film under 10 GHz frequency conditions is not higher than 3.20, and the dielectric loss is not higher than 0.0060; and / or, the CTE of the polyimide film is 19-25 ppm / K; More preferably, in the Lab value of the polyimide film, L is 50~70, a is 20~40, and b is -15~5; and / or, the dielectric constant of the polyimide film under 10GHz frequency conditions is not higher than 3.10, and the dielectric loss is not higher than 0.0050; and / or, the CTE of the polyimide film is 21~23ppm / K.

6. A polyimide laminate, characterized in that: include: a first polyimide layer; a second polyimide layer covering the surface of the first polyimide layer; and a third polyimide layer covering the surface of the second polyimide layer; Each layer of the polyimide laminate comprises the polyimide according to any one of claims 1 to 4 or the polyimide film according to claim 5, wherein the main body of the first polyimide layer and the third polyimide layer is polyimide 1, the main body of the second polyimide layer is polyimide 2, and in the structural unit of the polyimide 2, at least one of Ar and R1 to R8 contains a trifluoromethyl group; the fluorine content of the polyimide 2 is greater than 20%; Preferably, in the Lab value of the polyimide laminate, L is 50 to 80, a is 10 to 40, and b is -15 to 20; And / or, the dielectric constant of the polyimide laminate under the condition of 10 GHz frequency is not higher than 3.20, and the dielectric loss is not higher than 0.0060; and / or, the dielectric constant of the first polyimide layer and the third polyimide layer under the condition of 10 GHz frequency is 3.00-3.30, and the dielectric loss is 0.0040-0.0060; and / or, the dielectric constant of the second polyimide layer under the condition of 10 GHz frequency is 2.85-3.05, and the dielectric loss is 0.0050-0.0065; and / or, the CTE of the polyimide laminate is 19-25 ppm / K; and / or, the CTE of the first polyimide layer and the third polyimide layer is greater than 17.5 ppm / K and greater than the CTE of the second polyimide layer; preferably, the CTE of the first polyimide layer and the third polyimide layer is 30-65 ppm / K; and / or, the CTE of the second polyimide layer is 5-17 ppm / K; More preferably, in the Lab value of the polyimide laminate, L is 50-70, a is 20-40, and b is -15-5; and / or, the dielectric constant of the polyimide laminate under 10 GHz frequency conditions is not higher than 3.10, and the dielectric loss is not higher than 0.0050; and / or, the dielectric constant of the first polyimide layer and the third polyimide layer under 10 GHz frequency conditions is 3.00-3.20, and the dielectric loss is 0.0040-0.0 055; and / or, the dielectric constant of the second polyimide layer under 10 GHz frequency conditions is 2.85-3.00, and the dielectric loss is 0.0050-0.0060; and / or, the CTE of the polyimide laminate is 21-23 ppm / K; and / or, the CTE of the first polyimide layer and the third polyimide layer is 35-55 ppm / K; and / or, the CTE of the second polyimide layer is 7-15 ppm / K.

7. The polyimide laminate according to claim 6, characterized in that: The polyimide 2 comprises a structural unit represented by formula (3): Formula (3).

8. The polyimide laminate according to claim 6 or 7, characterized in that: In the polyimide 2, the molar percentage of the structural unit represented by formula (3) is 20% to 50%; Preferably, the polyimide 2 further comprises a structural unit represented by formula (4) and / or formula (5): Formula (4) Formula (5) In the formula, R1 to R8 are each independently a hydrogen atom, a fluorine atom, a trifluoromethyl group, a chlorine atom or a trichloromethyl group, and at least one of R1 to R8 is not a hydrogen atom.

9. The method for preparing a polyimide laminate according to any one of claims 6 to 8, characterized in that: The method comprises forming a first polyimide layer, a second polyimide layer and a third polyimide layer on a substrate to obtain a polyimide laminate; preferably comprising the following steps: 1) preparing a precursor solution of the polyimide 1 and a precursor solution of the polyimide 2 respectively; 2) coating a portion of the precursor solution of the polyimide 1 on a substrate and drying it, and then simultaneously casting and coating the precursor solution of the polyimide 2 and the remaining precursor solution of the polyimide 1 on the obtained precursor dry film layer and drying them to obtain a precursor dry film layer of the polyimide laminate; 3) thermally curing the substrate coated with the precursor dry film layer of the polyimide laminate; Preferably, step 1) comprises mixing a diamine with a solvent to obtain a solution; then adding dianhydride and reacting; and / or, the diamine accounts for 7% to 15% of the total mass of the solution; and / or, the reaction temperature is 0 to 50° C.; and / or, the ratio of the amount of the dianhydride to the amount of the diamine is 0.960≤≤1.100; And / or, in step 2), the substrate comprises copper foil, aluminum foil, steel strip or polymer support film, the drying temperature is 100-180° C., and the total solvent content in the precursor dry film layer is 15-35wt%; And / or, in step 3), the thermal curing temperature is 350-400°C.

10. A flexible copper clad laminate, characterized in that: It comprises a copper foil and a polyimide layer covering the surface of the copper foil; the polyimide layer is the polyimide film according to claim 5, the polyimide laminate according to any one of claims 6 to 8, or the polyimide laminate obtained by the preparation method according to claim 9; preferably, the difference between the CTE of the polyimide laminate and the CTE of the copper foil is not greater than 8ppm / K.

Citation Information

Patent Citations

  • Multilayered polyimide film having a low dielectric constant, laminate structure including the same and manufacture method thereof

    CN104691066A

  • Low-color polymers for flexible substrates in electronic devices

    CN110892003A

  • Method for preparing polyamic acid, and polyamic acid, polyimide resin and polyimide film manufactured thereby

    CN111542562A

  • Polyimide resin, polyimide film, preparation method of polyimide film and copper-clad plate

    CN114854012A

  • White polyimide film

    JP2010031258A